Penerapan Project Based Learning (PjBL) Dalam Meningkatkan Kemampuan Menulis Teks Cerpen - Anti, Amri; Sultan, Sultan; Sakaria, Sakaria (Fakultas Teknik Universitas Negeri Makassar, 2025)
This study aims to describe the application of Project-Based Learning (PjBL) in learning to write short story text for seventh-grade students of SMP Negeri 18 Makassar. The research method used is classroom action research. The implementation of this research uses two or more cycles, where each cycle has four stages, including planning, action implementation, observation, and reflection. The population in this study included the total number of seventh-grade students of SMP Negeri 18 Makassar, namely 288 students. Determination of the number of samples was carried out using the purposive sampling method. The chosen sample comprises 32 students from class VII.1. The data collected were analyzed using descriptive statistics. The results of learning to write short story texts using the Project-Based Learning (PjBL) model showed a significant increase. This is known after the results of the short story text writing test in cycle I; only four students obtained a score ≥ 80. While in cycle II, there were only 7 students who obtained < 80 out of 32 students. So that the improvement in students' ability to write short story texts using the Project-Based Learning (PjBL) model is categorized as successful based on the level of student completeness in cycle II, which reached 78%. Project-Based Learning (PjBL) in learning can facilitate students in writing short story texts.